2021
DOI: 10.1107/s1600576721007068
|View full text |Cite
|
Sign up to set email alerts
|

Bubble-induced fast crystal growth of indomethacin polymorphs in a supercooled liquid

et al.

Abstract: Physical stability is one of the main challenges when developing robust amorphous pharmaceutical formulations. This article reports fast crystal growth behaviors of the γ and α forms of indomethacin (IMC) initiated by bubbles in the interior of a supercooled liquid. Bubble-induced crystal growth of γ-IMC exhibits approximately the same kinetics as its surface crystal growth, supporting the view that bubble-induced crystal growth is a surface-facilitated process. In contrast, the rates of bubble-induced crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…These results support the view that crystal nucleation can be significantly enhanced by cooling the liquid to cause fracture (Su et al, 2019). Fracture was expected to generate a free surface, providing the sites for heterogeneous nucleation and enhanced molecular mobility (Shi, Tao et al, 2020;Shi et al, 2021;Su et al, 2019).…”
Section: Effects Of Pvp K90 On Fracture and Its Connections With Crys...supporting
confidence: 78%
See 3 more Smart Citations
“…These results support the view that crystal nucleation can be significantly enhanced by cooling the liquid to cause fracture (Su et al, 2019). Fracture was expected to generate a free surface, providing the sites for heterogeneous nucleation and enhanced molecular mobility (Shi, Tao et al, 2020;Shi et al, 2021;Su et al, 2019).…”
Section: Effects Of Pvp K90 On Fracture and Its Connections With Crys...supporting
confidence: 78%
“…Bubble-induced crystal growth in the interior of amorphous pharmaceuticals was first reported in griseofulvin at temperatures from 130 to 150 � C (Shi, Tao et al, 2020;Shi & Cai, 2016). In subsequent studies, these interesting growth behaviors have also been found in the crystal growth of nimesulide and in the �-form and �-form of indomethacin (Shi et al, 2021;. This enhanced crystallization through the air-liquid interface was mainly attributed to the fast molecular diffusion at the surface and interface (Yu, 2016;Huang, Ruan et al, 2017).…”
Section: Formation Of Needle-like Crystal Growth In the Presence Of P...mentioning
confidence: 85%
See 2 more Smart Citations